Community identity politics of Brijo Lor society, Klaten in Ki Ageng Glego myth through Reog performance (Harmonia: Journal of Arts Research and Education, 2017)
This research is aimed to describe community identity politics of Brijo Lor society, Klaten in Ki Ageng Glego myth through Reog performance. The research questions are how is the community identity politics in Brijo Lor society, and what is the relationship between the identity politics with Ki Ageng Glego myth through Reog performance? The research approach used is qualitative. Data collecting technique was obtained by these ways: observation, documentation, literature, and interview. Data analysis was conducted by: data collection, data reduction, data diagnose, and conclusion. To ensure the validity of the data, the researcher conducted triangulation. The result of this research proposed that community identity politics in Brijo Lor society in preserveing Reog is a strategy to maintain traditional art for many other traditional arts are extinct. Reog performance conducted regularly is a mediationof the society who ngalap berkah (beg for blessing) to Ki Ageng Glego spirit. When Reog is performed, Ki Ageng Glego spirit descends upon the world. Many people come to watch Reog because they want to get blessing for the descend of Ki Ageng Glego spirit. Ki Ageng Glego myth became an identity political way of Brijo Lor society through Reog performance.